2011
DOI: 10.3168/jds.2010-3957
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ conservation of Holstein-Friesian cattle: Comparing the Dutch, French, and US germplasm collections

Abstract: Holstein-Friesian (HF) gene bank collections were established in France, the Netherlands, and the United States to conserve genetic diversity for this breed. Genetic diversity of HF collections within and between countries was assessed and compared with active male HF populations in each country by using pedigree data. Measures of genetic diversity such as probability of gene origin inbreeding and kinship were calculated. The cryobanks have captured substantial amounts of genetic diversity for the HF compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
3
33
0
3
Order By: Relevance
“…Finally, we showed that the sampling method used for the French National Cryobank is quite efficient despite the fact it is a fairly new tool, as all collections have a lower kinship with female than the AM * female kinship (Table 3). However, this kinship is quite higher than the kinship of the female population, which could be already considerate as high, so it seems crucial to protect the last straws from old AI bulls that might still exist as already stated in Danchin‐Burge et al. (2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, we showed that the sampling method used for the French National Cryobank is quite efficient despite the fact it is a fairly new tool, as all collections have a lower kinship with female than the AM * female kinship (Table 3). However, this kinship is quite higher than the kinship of the female population, which could be already considerate as high, so it seems crucial to protect the last straws from old AI bulls that might still exist as already stated in Danchin‐Burge et al. (2011).…”
Section: Discussionmentioning
confidence: 95%
“…Van Doormaal et al. 2005; Koenig & Simianer 2006; Kim & Kirkpatrick 2009; Danchin‐Burge et al. 2011).…”
Section: Introductionunclassified
“…The number of HF bulls in the gene bank is 144 for France, 3755 for the Netherlands and 5013 for the USA (Danchin‐Burge et al . ). For most livestock breeds under threat, such numbers cannot be reached, and hence, the number of animals selected in our study (20) is more relevant for small populations to be conserved in a gene bank.…”
Section: Discussionmentioning
confidence: 97%
“…It was also suggested that cryopreserved bio-specimens could be used as a backup material to redirect the selection scheme of a given breed, if needed [2,3]. Consequently, several gene banks have been created with different strategies and policies that vary with the breed, species, and country concerned [4,5] and methods have been proposed to use ex situ genetic resources to optimise the management of genetic diversity in endangered breeds [6]. Breeds with large populations are subject to high selection pressures and have rates of inbreeding greater than the desired values [7].…”
Section: Introductionmentioning
confidence: 99%